Circumferential velocities in laminar and turbulent counter-vortex flow - Orekhov Genrikh (E3S Web of Conferences, 2023)
Knowledge of the parameters of fluid movement is essential in the designing and operating various technological processes in various technical applications. These processes play a special role in hydro engineering, where the structures of water works are directly subjected to static and dynamic forces from the side of the water flow. The operation of hydraulic turbines, spillway and water transport systems, and other hydraulic structures is directly connected with understanding the behavior of a fluid in various regimes of movement. This report is devoted to the study of a special type of fluid and gas flow, which is called counter-vortex flow. The report compares the results of the distribution of circumferential velocities with a laminar and turbulent pattern of fluid movement. The results of the laminar flow regime were obtained using a mathematical model, and the turbulent regime on a physical model using laser technologies. Such a comparison allows one to assess two approaches in determining the kinematic structures of a complicated flow. The parameters for the viscous fluid laminar flow were determined based on the traditional system of Navier-Stokes equations by determining the dependence of the circumferential component of the total velocity at the given initial circulations and angular flow velocity. A physical model was made and equipped with a set of measuring equipment to obtain the distribution of velocities in the turbulent flow. The comparison showed that the distributions of velocities for the considered flow regimes depending on the channel radius have close coincidence. In contrast, the transformation length-wise of the active zone of the flow is significant.